The Effect of Time on the Disciplinary Adjustment of Women in Prison - Casey-Acevedo, Karen (International journal of offender therapy and comparative criminology, 2001)
The number of women in state and federal prisons has doubled in the past 10 years (from approximately 40,000 to more than 87,000), yet research on women in prisons is extremely limited, especially with regard to women in maximum-security institutions. Significant studies on women inmates have focused on inmates' adaptation to prison life and the development of kinship groups while incarcerated. A few studies have examined the disciplinary behavior of female inmates, by comparing female inmates with male inmates. However, there exists little research on the temporal patterns of disciplinary behavior among women inmates, which was the focus of this article